6-Morpholino- and 6-amino-9-sulfonylpurine derivatives. Synthesis, computational analysis, and biological activity. (1st March 2021) - Matić, Josipa; Jukić, Marijana; Ismaili, Hamit; Saftić, Dijana; Ban, Željka; Tandarić, Tana; Vianello, Robert; Opačak-Bernardi, Teuta; Glavaš-Obrovac, Ljubica; Žinić, Biserka
Abstract: The synthesis of novel 6-chloro/morpholino/amino/-9-sulfonylpurine derivatives was accomplished in two ways, either (i) involving the condensation reaction of 6-chloropurine with commercially available arylsulfonyl chlorides in acetone and the presence of aqueous KOH at 0 °C, followed by the substitution of C6-chlorine with morpholine, or (ii) employing a reversed synthetic approach where 6-morpholinopurine and commercially available adenine bases were reacted with the corresponding alkyl, 2-arylethene and arylsulfonyl chlorides giving the N9 sulfonylated products, the latter particularly used where prior nonselective sulfonylation was observed. In both approaches, the sulfonylation reaction occurred regioselectively at the purine N9 position lacking any concurrent N7 derivatives, except in the case of a smaller methyl substituent on SO2 and the free amino group at C6 of the purine ring. The tautomeric features of initial N9 unsubstituted purines, as well as stability trends among the prepared N -9-sulfonylpurine derivates, were investigated using DFT calculations with an important conclusion that electron-donating C6 substituents are beneficial for the synthesis as they both promote the predominance of the desired N9 tautomers and help to assure the stability of the final products. The newly synthesized 6-morpholino and 6-amino-9-sulfonylpurine derivatives showed antiproliferative activity on human carcinoma, lymphoma, and leukemia cells. Among the tested compounds, 6-morpholino 17 and 6-amino 22 derivatives, with trans - β -styrenesulfonyl group attached at the N9 position of purine, proved to be the most effective antiproliferative agents, causing accumulation of leukemia cells in subG0 cell cycle phase. Graphical Abstract: